Studi Kasus Audit Energi Dan Peluang Penghematan Energi Pada Plant Pulp Dryer 3 PT. Riau Andalan Pulp And Paper - Wahyu Syahputra; Zulfansyah Zulfansyah; Hari Rionaldo; Sri Wahdini Rahmi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Energy auditing is one of the steps made in an effort to realize energy saving programs. The energy widely used in the pulp and paper industries is thermal energy (steam). Pulp drying is one of the processes that many use such energy. The thermal energy used was of low to moderate pressurized steam, which was supplied into a number of rotating dryer cylinders. Evaporation is done because water can no longer be removed from the fiber by gravity and vacuum in the forming of the unit and mechanically in the pressing of the unit. The results of the study were found two “steam trap” units with “inverted” installation positions and four “steam trap” units as well as six “valve” units with “Passing" (leaking)” conditions that made “losses steam” of 467.8 Kg/hr or 1,467 tons of steam/year or about IDR 240.051,840 in a year. The inverse improvements/recovery of “steam trap” positions can save steam with a saving percentage of 0,34% of total steam costs per year and will return investment capital for four hours. Whereas the turnover on leaked “steam trap” units could save steam of 2,574 tons of steam/year with a savings percentage of 0.60% of total steam cost per year and would return investment capital for four months.Keywords : Pulp Dryer, Energy Consumption, Energy Saving, Steam Trap, Losses Steam